A spectroscopic approach for rapid and simple serial number restoration on polyamide 6 parts of firearms: The use of video spectral comparator 8000. Issue 6 (19th June 2021) - Uysal, Serdar; Armutcu, Canan; Mercan, Mustafa; Uzun, Lokman
Abstract: Serial numbers have forensic value as they help to identify firearms. While the serial numbers are mostly stamped on the metal parts of firearms, the characters on polymer parts involve non‐serial number information such as caliber, brand, model, or proof marks, which also serve for identification purposes. The forensic evidence indicates that the polymer frames of firearms bearing non‐serial number information are obliterated through heating and scraping. Although the destructive restoration techniques for polymers are well‐documented, there is little theoretical and practical knowledge regarding the non‐destructive restoration techniques applied on polymers. In view of this gap, this study aims to devise a non‐destructive spectral technique to recover the obliterated characters on Polyamide 6. Considering its wide use on polymers, the numbering is carried out by hot stamping and the numbers are defaced through heating, scraping, and hammering both superficially and deeply at varying depths. Herein, we focused on imitating the manual obliteration techniques used by criminals instead of the deepness‐controlled techniques preferred by previous studies. The samples are then viewed under the UV and IR lights in the Video Spectral Comparator 8000 for the first time. The results suggest that spectral imaging provided restoration to a good extent after heating and scraping which made the characters invisible at a relatively low depth of deformation compared to hammering. The recovery of characters with this novel technique brings a new perspective forensic marks examination literature by producing quick, successful and reliable results and facilitating reexamination by not harming the sample.